KEKERASAN POLITIK ATAS NAMA AGAMA DAN PERAN KYAI DALAM KONSTELASI POLITIK DAERAH: MENELUSURI AKAR KONFLIK JEPARA 7 JULI 1998 - hidayatullah rabbani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
The Jepara riot on July 7, 1998 was one of the impacts of the reforms at the local level that began in May in the same year. This riot has claimed lives, significant material and immaterial losses. The cause of this riot was the politicization of religion in the political field. To study this problem, the critical historical method is used which includes four steps, namely heuristics, criticism, synthesis and historiography. The data mining technique uses written primary sources in the form of archives from other contemporary reports, such as newspapers and magazines. Oral primary sources are obtained through direct interviews with competent people. Secondary sources are obtained through literature study of books by relevant scholars and experts or other forms of publication. The results showed that the role of the Kyai in politics in Jepara was very large in directing his followers to determine their political direction. The emergence of a plan to form a new party among NU residents has divided Jepara society. The culmination of this split led to the rioting on July 7 1998. This paper is a development of the author's thesis entitled Kyai, Politics, and Violence: Riots in Jepara 1998.